(untitled) - Holeš, Jan (Romanica Olomucensia, 2012)
The article deals with French-based creoles, with a special attention paid to those spoken on the islands in the Indian Ocean. These include the creole languages used in two independent countries, the Republic of Mauritius (and Rodrigues, its dependency) and the Republic of Seychelles, and in the French overseas department of Réunion. The article contains samples of the respective creole languages and some illustrations of their use.
Keywords: Creole; Indian Ocean; Mauritius; Rodrigues; Seychelles; Réunion.